Description of Immuno-Morphological Characteristics of Cervical Cancer and their Interrelationships - Ramazonovich, Abraykulov Ilhom; Abduqayumovich, Eshmuradov Elbek (American Journal of Biodiversity, 2025)
Human papillomavirus (HPV) is the leading cause of cervical precancerous lesions (CPC) among women of reproductive age worldwide, with a mortality rate of 75% from the disease and its complications.